ROM Therapy on Muscle Strength in Post Stroke Patients: Scoping Review - Muliyani Yamlean; Chandra Bagus Ropyanto; Fitria Handayani (Indonesian Journal of Global Health Research, 2021)
Hemiparesis and hemiplegia are motor deficits found mostly in stroke patients. If the deterioration in muscle strength that occurs is not handled properly, it will cause permanent disability. ROM therapy is a therapy to increase muscle strength which has undergone various developments according to the research that has been done. The aim of this article was to identify interventions using ROM therapy to improve muscle strength in post-stroke patients. The databases used were JCS, PMC, Science Direct, and PubMed. The search was limited to articles published in 2014 to 2019. The study criteria was for adult, quantitative comparisons between before and after intervention ROM therapy and full text article, published in peer-reviewed journal and written in English and Indonesian. This article used the methodological framework by Arksey and O'Malley for the scoping review. The research has conducted a study of 4 articles, in which all of the items discussed the application of ROM therapy to increase muscle strength in post-stroke patients. The results from each articles showed that ROM therapy has helped improve muscle strength in post-stroke patients.